2021
DOI: 10.3390/medicina57111250
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of General and Spinal Anaesthesia on Systemic Inflammatory Response in Patients Undergoing Total Knee Arthroplasty: A Propensity Score Matching Analysis

Abstract: Background and Objectives: Some of the postoperative complications following orthopaedic surgeries are associated with a systemic inflammatory response (SIR), which varies depending on the anaesthetic technique. We aimed to compare the effects of general and spinal anaesthesia on the SIR after total knee arthroplasty (TKA), based on C-reactive protein (CRP) levels, the platelet-lymphocyte ratio (PLR), and the neutrophil-lymphocyte ratio (NLR). Materials and Methods: Patients who underwent TKA between January 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 29 publications
0
6
1
Order By: Relevance
“…Several studies have claimed many benefits of RA, such as reducing wound infections, transfusions, thromboembolic events, including MI and stroke, length of stay, and operation time. [8][9][10][11] However, other researchers have reported that there is no significant difference in the serious adverse events, including thromboembolic events and surgical site infections, transfusions, and length of stay between RA and GA. [12][13][14] In this study, contrary to our expectations, 30-day mortality, transfusion rate, hospital stay, and most complications, including delirium, were not significantly different between the GA and RA groups. This may be due to the overall decline in the incidence of complications with advances in the management of patients receiving TKA.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…Several studies have claimed many benefits of RA, such as reducing wound infections, transfusions, thromboembolic events, including MI and stroke, length of stay, and operation time. [8][9][10][11] However, other researchers have reported that there is no significant difference in the serious adverse events, including thromboembolic events and surgical site infections, transfusions, and length of stay between RA and GA. [12][13][14] In this study, contrary to our expectations, 30-day mortality, transfusion rate, hospital stay, and most complications, including delirium, were not significantly different between the GA and RA groups. This may be due to the overall decline in the incidence of complications with advances in the management of patients receiving TKA.…”
Section: Discussioncontrasting
confidence: 99%
“…Several studies have claimed many benefits of RA, such as reducing wound infections, transfusions, thromboembolic events, including MI and stroke, length of stay, and operation time. [8–11] However, other researchers have reported that there is no significant difference in the serious adverse events, including thromboembolic events and surgical site infections, transfusions, and length of stay between RA and GA. [12–14]…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…An interpretation on the effect of anesthetic practice on post-operative natural killer T-lymphocytes also declared no difference in the nerve block anesthesia group comparison to the general anesthesia group (12).…”
Section: Introductionmentioning
confidence: 99%